2012
DOI: 10.1038/pcan.2012.22
|View full text |Cite
|
Sign up to set email alerts
|

AST-induced bone loss in men with prostate cancer: exercise as a potential countermeasure

Abstract: Androgen suppression treatment (AST) for men with prostate cancer is associated with a number of treatment-related side effects including an accelerated rate of bone loss. This loss of bone is greatest within the first year of AST and increases the risk for fracture. Pharmaceutical treatment in the form of bisphosphonates is currently used to counter the effects of hormone suppression on bone but is costly and associated with potential adverse effects. Recently, exercise has been shown to be an important adjuv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 100 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…Aerobic exercise consisted in walking or using the elliptical machines, while resistance-training included upper and lower body resistance exercises provided through use of body weight, dumbbells, elastic bands [ 18 ]. Physical exercise may also play an important role in reducing bone loss and preventing fracture risk in prostate cancer patients treated with androgen suppression treatment [ 19 ].…”
Section: Physical Aspectsmentioning
confidence: 99%
“…Aerobic exercise consisted in walking or using the elliptical machines, while resistance-training included upper and lower body resistance exercises provided through use of body weight, dumbbells, elastic bands [ 18 ]. Physical exercise may also play an important role in reducing bone loss and preventing fracture risk in prostate cancer patients treated with androgen suppression treatment [ 19 ].…”
Section: Physical Aspectsmentioning
confidence: 99%
“…It has been reported that within the first three to 12 months of ADT, men experience losses in lean mass and muscle strength of up to 5% [21,194,346,347] and 11% [25,28,29] , respectively, which may partially contribute to the observed 23-65% increased fracture risk in this group [202,214,348] . There is also a profound gain (up to 15%) in fat mass which likely contributes to the 10-45% reported increased risk of diabetes, coronary heart disease, myocardial infarction and sudden cardiac death [207,220,333,346,349,350] .…”
Section: Introductionmentioning
confidence: 99%
“…13,14 In addition, cancer patients are also more vulnerable to other chronic comorbidities such as cardiovascular disease, diabetes, osteoporosis, and sarcopenia. [15][16][17] Therefore, strategies that can reduce the risk of cancer and mitigate a wide range of health sequelae related to the disease and its treatments are of clinical importance.…”
Section: Introductionmentioning
confidence: 99%